2019
DOI: 10.11648/j.ajaf.20190706.14
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Characteristics and Antioxidant Activity of Cocoa Vinegar During Fermentation of Pulp Liquids by Adding <i>Tape</i> Yeast

Abstract: The pulp liquids as a by-product of cocoa beans fermentation is potential to be used as a raw material for making cocoa vinegar, but unfortunately the content of acetic acid is relatively low and there have been no studies related to antioxidant activities. The objectives of the present study were to examine the effect of addition of tape yeast and fermentation time of pulp liquids to the changes of characteristics and antioxidant activities of cocoa vinegar and to define the best treatments of the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Additionally, factors such as the raw material, production, and storage may influence these characteristics as well. (CASALE et al, 2006;XU et al, 2007;GANDA-PUTRA et al, 2019) In addition to acting as antioxidants, phenolic compounds are responsible for the color and astringency of vinegars. In a study by HORNEDO-ORTEGA et al (2017), it was observed that oxidation changed the color of alcoholically fermented strawberry, which was directly correlated to the decrease in anthocyanins.…”
Section: Color Parameters and Phenolic And Total Carotenoid Compounds For Pulp Alcoholic Fermentation And Vinegarmentioning
confidence: 99%
“…Additionally, factors such as the raw material, production, and storage may influence these characteristics as well. (CASALE et al, 2006;XU et al, 2007;GANDA-PUTRA et al, 2019) In addition to acting as antioxidants, phenolic compounds are responsible for the color and astringency of vinegars. In a study by HORNEDO-ORTEGA et al (2017), it was observed that oxidation changed the color of alcoholically fermented strawberry, which was directly correlated to the decrease in anthocyanins.…”
Section: Color Parameters and Phenolic And Total Carotenoid Compounds For Pulp Alcoholic Fermentation And Vinegarmentioning
confidence: 99%